2017
DOI: 10.1097/ico.0000000000001323
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Small Incision Lenticule Extraction: Challenges and Complications

Abstract: The learning curve of SMILE is surgically challenging. Lenticule dissection and extraction is the most difficult step and leads to a multitude of complications. Most complications that result in delayed visual recovery are observed in the initial 50 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 17 publications
1
68
0
2
Order By: Relevance
“…However, the steep learning curve of SMILE may prove to be challenging especially for beginners. 11 , 12 A stepwise approach consisting of observation, initial wetlab training, and flap-based refractive lenticule extraction (femtosecond lenticule extraction [FLEx] and pseudo-SMILE) may help to familiarize the novice surgeon with lamellar separation and handling the refractive lenticule. 1 , 11 , 13 A high incidence of intraoperative complications may be observed during the initial learning phase, and the majority of these are a result of difficult lenticule dissection and extraction.…”
Section: Introductionmentioning
confidence: 99%
“…However, the steep learning curve of SMILE may prove to be challenging especially for beginners. 11 , 12 A stepwise approach consisting of observation, initial wetlab training, and flap-based refractive lenticule extraction (femtosecond lenticule extraction [FLEx] and pseudo-SMILE) may help to familiarize the novice surgeon with lamellar separation and handling the refractive lenticule. 1 , 11 , 13 A high incidence of intraoperative complications may be observed during the initial learning phase, and the majority of these are a result of difficult lenticule dissection and extraction.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison with other studies, a literature review was performed to find all reports of suction loss in SMILE. Twenty-two studies were identified and the suction loss incidence is summarized in Table 5 Wang et al 2013Wang et al , 2014Wang et al , 2017Ganesh & Gupta 2014;Ivarsen et al 2014;Sekundo et al 2014;Wong et al 2014, Kamiya et al 2015Ramirez-Miranda et al 2015;Xu & Yang 2015;Donate & Thaeron 2016;FDA, 2016;Liu et al 2016;Osman et al 2016;Pradhan et al 2016;Yildirim et al 2016; Gab-Alla 2017; Park & Koo 2017;Pedersen et al 2017;Taneri et al 2017;Titiyal et al 2017;Damgaard et al 2018). For studies with large populations of more than 1500 procedures (Ivarsen et al 2014;Liu et al 2016;Osman et al 2016;Pradhan et al 2016;Park & Koo 2017;Wang et al 2017), the incidence was similar to the 0.50% in the current study, ranging from 0.17% (Pradhan et al 2016) to 0.20% (Park & Koo 2017), 0.41% (Liu et al 2016), 0.78% (Ivarsen et al 2014), up to 0.93% (Wang et al 2017), and a highest value of 2.10% (Osman et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Lenticule dissection and extraction is the most challenging step and can lead to complications, such as tear of anterior cap or side cut, posterior stromal damage, and partially or completely retained lenticule [39]. However, these complications are related to inexperience and may decrease with the learning curve [37,39].…”
Section: Refractive Lenticule Extraction (Relex)mentioning
confidence: 99%
“…Lenticule dissection and extraction is the most challenging step and can lead to complications, such as tear of anterior cap or side cut, posterior stromal damage, and partially or completely retained lenticule [39]. However, these complications are related to inexperience and may decrease with the learning curve [37,39]. Complications, including suction loss, incisional bleeding, OBL, and inaccurate laser pulse placement, have also been reported; however, these can mostly be resolved with appropriate management [40].…”
Section: Refractive Lenticule Extraction (Relex)mentioning
confidence: 99%